Synthesis of citric acid functionalized magnetic graphene oxide coated corn straw for methylene blue adsorption. (December 2016) - Ge, Heyi; Wang, Cuicui; Liu, Shanshan; Huang, Zhen
Graphical abstract: The schematic illustration of preparing CA-mGOCS and adsorption MB process. Highlights: The CA-mGOCS was synthesized for the removal of MB from aqueous solution. The adsorption performance obeyed the pseudo-second-order and Freundlich models. The adsorption mechanism was a spontaneous, exothermic and randomness decrease process. CA-mGO5CS had an excellent reproducibility. Abstract: The citric acid functionalized magnetic graphene oxide coated corn straw (CA-mGOCS) as a new adsorbent was synthesized in this work for the elimination of methylene blue (MB) from waste water. The as-prepared CA-mGOCS was tested by SEM, FTIR, XRD, Roman spectrum, TGA, particle size analyzer, BET and magnetic properties analyzer. Some factors affecting adsorption removal efficiency were explored. As a result, the addition of 5 g CS (CA-mGO5CS) had the better adsorption performance than other adsorbents. The pseudo-second-order model and the Freundlich described the adsorption behavior well. The equilibrium adsorption capacity was 315.5 mg g −1 for MB at pH = 12 and 298 k. The electrostatic incorporation as well as hydrophobic interactions between CA-mGO5CS and MB determined the favourable adsorption property. Besides, the thermodynamic studies results ΔG < 0, ΔH < 0, ΔS < 0 suggested that the adsorption was a spontaneous, exothermic and randomness decrease process. Finally, reusability studies imply that CA-mGO5CS has an excellent reproducibility.